Restricted Feeding Schedules Modulate in a Different Manner the Expression of Clock Genes in Rat Hypothalamic Nuclei - De Araujo, Leonardo D.; Roa, Silvia L.; Bueno, Ana C.; Coeli-Lacchini, Fernanda B.; Martins, Clarissa S.; Uchoa, Ernane T.; Antunes-Rodrigues, Jose; Elias, Lucila L.; Elias, Paula C.; Moreira, Ayrton C.; De Castro, Margaret (Frontiers in Neuroscience, 2016)
Food access restriction is associated to changes in gene expression of the circadian clock system. However, there are only a few studies investigating the effects of non-photic synchronizers, such as food entrainment, on the expression of clock genes in the central oscillators. We hypothesized that different feeding restriction patterns could modulate the expression of clock genes in the suprachiasmatic nucleus (SCN) “master” clock and in extra-SCN oscillators such as the paraventricular (PVN) and arcuate (ARC) hypothalamic nuclei. Wistar rats were divided into four groups: Control group (CG; food available ad libitum), Restricted night-fed (RF-n; food access during 2 hours at night), Restricted day-fed (RF-d; food access during 2 hours at daytime), Day-fed (DF; food access during 12 hours at daytime). After 21 days, rats were decapitated between ZT2-ZT3 (0800-0900h); ZT11-ZT12 (1700-1800h), or ZT17-18 (2300-2400h). Plasma corticosterone was measured by radioimmunoassay (RIA). The expression of Clock, Bmal1, Per1, Per2, Per3, Cry1, Cry2, Rev-erbα, and Rorα were assessed in SCN, PVN, and ARC hypothalamic nuclei by RT-PCR and calculated by the 2[-Delta Delta CT(Cycle threshold)](2-ΔΔCT) method. Restricted food availability during few hours led to decreased body weight in RF-n and RF-d groups compared to controls and DF group. We also observed an anticipatory corticosterone peak before food availability in RF-n and RF-d groups. Furthermore, the pattern of clock gene expression in response to RF-n, RF-d, and DF schedules was affected differently in the SCN, PVN, and ARC hypothalamic nuclei. In conclusion, the master oscillator in SCN as well as the oscillator in PVN and ARC, all brain areas involved in food intake, responds in a tissue-specific manner to feeding restriction.